Management of pediatric low-grade glioma. Issue 1 (February 2019) - de Blank, Peter; Bandopadhayay, Pratiti; Haas-Kogan, Daphne; Fouladi, Maryam; Fangusaro, Jason
Abstract : Purpose of review: Pediatric low-grade gliomas (pLGGs) have been treated with similar therapies for the last 30 years. Recent biological insights have allowed a new generation of targeted therapies to be developed for these diverse tumors. At the same time, technological advances may redefine the late toxicities associated with radiation therapy. Understanding recent developments in pLGG therapy is essential to the management of these common pediatric tumors. Recent findings: It is now well understood that aberrations of the mitogen-activated protein kinase pathway are key to oncogenesis in low-grade gliomas. This understanding, along with the development of available targeted agents, have heralded a new era of understanding and treatment for these patients. Promising, sustained responses are now being seen in early phase trials among patients with multiply recurrent/progressive disease. Also, newer and highly conformal radiation approaches such as proton beam radiotherapy maintain efficacy of radiation but limit radiation-associated toxicities. Summary: Novel therapies offer the potential for tumor control with greatly reduced toxicities. However, late effects of these therapies are just now being explored. Improved radiation approaches and targeted agents have the potential to redefine traditional therapy for pLGG.